2013
DOI: 10.5812/iranjradiol.6353
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nasal Bone Fractures on Conventional Radiography and Facial CT: Comparison of the Diagnostic Accuracy in Different Imaging Modalities and Analysis of Interobserver Reliability

Abstract: BackgroundThere has been no study to compare the diagnostic accuracy of an experienced radiologist with a trainee in nasal bone fracture.ObjectivesTo compare the diagnostic accuracy between conventional radiography and computed tomography (CT) for the identification of nasal bone fractures and to evaluate the interobserver reliability between a staff radiologist and a trainee.Patients and MethodsA total of 108 patients who underwent conventional radiography and CT after acute nasal trauma were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…In total, there were three additional fractures detected by CT. Similar results were found in a study by Baek et al, [19] where unilateral and bilateral simple displaced fractures formed 69.3% of total cases (88). They showed that accuracy of nasal bone X-ray in detection of fracture ranged from 66% to 76%.…”
Section: Discussionsupporting
confidence: 91%
“…In total, there were three additional fractures detected by CT. Similar results were found in a study by Baek et al, [19] where unilateral and bilateral simple displaced fractures formed 69.3% of total cases (88). They showed that accuracy of nasal bone X-ray in detection of fracture ranged from 66% to 76%.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, nasal bone with mandible fractures was less associated with falls, (OR: 0.085, 95% CI: 0.01‐0.57, P = .0125), which may be due to a single, localized impact of relatively lower velocity that protects the midface. Most patients at the study institution underwent maxillofacial CT as part of their workup (85%), which is higher than other series . The rate of CT is likely higher in regional level 1 trauma centers, given the severity and scope of presenting injuries in this population.…”
Section: Discussionmentioning
confidence: 86%
“…Most patients at the study institution underwent maxillofacial CT as part of their workup (85%), which is higher than other series. 6,29 The rate of CT is likely higher in regional level 1 trauma centers, given the severity and scope of presenting injuries in this population.…”
Section: Epidemiologymentioning
confidence: 99%
“…These studies are further limited by their inability to detect cartilaginous injuries, which are more prevalent in pediatric cases. 4,6 For this reason, it is very important to have a radiologist with experience in nasal bone X-rays and to combine the lateral view with a frontal Waters view. In our country (Chile), X-rays have a legal importance, because as we show in this study, if they are informed correctly by a qualified specialist, they have an adequate diagnostic capability.…”
Section: Discussionmentioning
confidence: 99%